FREQUENCY OF SPONTANEOUS MISCARRIAGES IN OBESE AND NON-OBESE WOMEN - UROOJ , A; KHAN , SA; AWAN , F (Biological and Clinical Sciences Research Journal, 2024)
Miscarriages are a common complication of pregnancy, affecting approximately 12-15% of all clinically recognized pregnancies in the general population. However, the exact frequency of miscarriages is unknown as they often occur before a woman is aware of her pregnancy. The main objective of this study was to determine the frequency of spontaneous miscarriages in pregnant women and to compare the frequency between obese and non-obese women. This cross-sectional study was conducted in the Gynecology Department of Lady Reading Hospital in Peshawar from November 16, 2019, to November 16, 2020. During this study, 140 patients were observed, and dates calculated their gestation period. A P/V examination was conducted, and a TVS or Pelvic ultrasound was performed to confirm the diagnosis of spontaneous miscarriage. Informed consent was obtained after the diagnosis, and data was collected using an attached Performa. The mean age of the patients in this study was 29 years, with a standard deviation of ± 7.714. Forty-one percent of the patients were primigravida, while 59% were multigravida. The study revealed that the frequency of spontaneous miscarriages was 12% among pregnant women. Furthermore, the incidence of spontaneous miscarriages was more common in obese pregnant women compared to non-obese pregnant women.